Adaptation and validation of a translated questionnaire assessing public awareness, knowledge, attitudes, and practices regarding antibiotic use in Malaysia - Che Hasan, Muhammad Kamil; Firdaus, Mohd Khairul Zul Hasymi; Nik Mohd Hatta, Nik Noor Kaussar; Thandar Soe, Sumaiyah Jamaludin; Mahat, Nur Ain; Sidek Ahmad, Zulkhairul Naim; Triastuti, Efta; Fang Fang, Kow; Abdul-Hamid, Shidqiyyah (Shahrekord University of Medical Sciences, 2025)
Background and aims: Antibiotic misuse is an escalating global health concern, especially in Malaysia, resulting in increased resistance and significant public health challenges. Understanding the public’s awareness, knowledge, attitudes, and practices (AKAP) regarding antibiotic use is essential for implementing effective interventions. Therefore, this study aimed to adapt and validate a questionnaire derived from existing tools and translated from English to Malay to assess the AKAP related to antibiotic use among the Malaysian public.